Implementation of performance assessment in STEM-based science learning to improve students’ habits of mind - M. Yakob; H. Hamdani; R. P. Sari; A. G. Haji; N. Nahadi (Institute of Advanced Engineering and Science, 2021)
This study described the implementation of STEM-based science learning and performance assessment to the improvement of students’ thinking skill in Aceh, Indonesia. The purposive sampling technique was employed in this descriptive research. The respondents were 300 students at grade 11th academic year 2019/2020 which representing five public high schools in Aceh, Indonesia. The instruments used to measure the effectiveness of the implementation of STEM-based science learning were the rubric of habits of mind, observation sheets of performance assessments, and questionnaires. The finding presented the implementation of STEM-based science learning was able to habituate and develop students' habits of mind with an average score of 0.71 which included into high category. The average value of the overall STEM-based science learning implementation for the formation of habits of mind is 95.98% which categorized as good. It can be concluded that there is the success of researchers in implementing STEM-based science learning to form students' habits of mind.